Mediating role of access to finance on the relationship between strategic orientation and SMES performance in Nigeria: A proposed research framework - Aminu, Ibrahim Murtala; Mohd Shariff, Mohd Noor (Society of Scientific Research and Education (SSRE), 2014)
Even thoughthe importance of SMEs ininfluencing economic growthis acknowledged, Nigerian enterprises performance is not as anticipated. The low contribution to GDP and employment shows a gross underperformance. Besides, SMEs high failure rate is another indication of low performance. However, inadequate access to finance occupies a central position for the low performance of SMEs in Nigeria. Similarly, previous studies suggest that strategic orientations have a significant influence on firm performance, even though the role of access to finance in understanding the mechanism through which these variables are related is neglected.Hence, this paper aims to undertake a review of the related literature to develop and propose a research conceptual framework for SMEs performance.Based on the combination of four strategic orientations and the role of access to finance, this study proposes that access to finance may further explain the relationship.It highlights the importance of the research on the relationship between entrepreneurial orientation, market orientation, learning orientation, technology orientation, access to finance and SMEs performance in Nigeria.